Quantitative Method for Detecting Vibrio Species Using Bio-Theta DOXTM System - Tanno, Shouichi; Fukui, Naoki; Utaka, Yukihiro; Ohkawa, Saburo; Morita, Yukio; Boonmar, Sumalee (The Thai Journal of Veterinary Medicine, 2014)
This is the first report of a quantitative method for detecting Vibrio species using the Bio-Theta DOXTM system. We assessed 19 strains of 9 Vibrio species and 22 strains of 22 non-Vibrio species and found that the positive rate in the medium-concentration (103 cfu/ml) and low-concentration (10 cfu/ml) samples of the 19 Vibrio samples was 100% and 89.5% (17/19), respectively. A few low-concentration samples of V. alginolyticus and V. vulnificus were negative. All Vibrio strains displayed good linear calibration curves for detection time vs bacterial count (r>0.94). The negative rate of the high-concentration (106 cfu/ml) and medium-concentration (103cfu/ml) samples of the 22 non-Vibrio samples was 86.4% (19/22) and 95.5% (21/22), respectively. Three positive non-Vibrio samples identified by the DOX system were Pseudomonas aeruginosa in medium- and high-concentration samples and Enterobacter cloacae and Proteus mirabilis in high-concentration samples. Shrimp are most often infected by Vibrio species. Microbial flora of shrimp farming pond has not been understood completely in South-east Asia, however, the bacterial counts in environmental water such as river, sea, ponds and wastewater treatment field are usually made in medium-concentration samples. In addition, the detection time for P. aeruginosa was notably longer than that for many of the Vibrio species. As the next step, although a Vibrio field detection study is needed, monitoring total Vibrio counts using the DOX system may become a useful means for early precautions against infectious diseases relating Vibrio species.